Matrix and determinant : fundamentals and applications - Shah, Nita H.; Thakkar, Foram A. (Boca Raton : CRC Press, 2020)
This book provides a clear understanding regarding the fundamentals of matrix and determinant from introduction to its real-life applications. The topic is considered one of the most important mathematical tools used in mathematical modelling. Matrix and Determinant: Fundamentals and Applications is a small self-explanatory and well synchronized book that provides an introduction to the basics along with well explained applications. The theories in the book are covered along with their definitions, notations, and examples. Illustrative examples are listed at the end of each covered topic along with unsolved comprehension questions, and real-life applications. This book provides a concise understanding of matrix and determinate which will be useful to students as well as researchers.
OCLC-licensed vendor bibliographic record.
Keywords: Determinants; Matrices; MATHEMATICS / Applied; TECHNOLOGY / Operations Research; BUSINESS & ECONOMICS / Operations Research